Fabrication of Poly(o-Chloroaniline) to MMT Clay as Potential Flame-Resistant Material - Iqbal, Shahid; Nadeem, Sohail; Ahmad, Mirza Nadeem; Javed, Mohsin; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Elkaeed, Eslam B.; Alshammari, Fwzah H.; Alwadai, Norah; Alahmdi, Mohammed Issa; Bahadur, Ali; et al. (Frontiers in Materials, 2022)
Graphical Abstract